EVALUASI ESTETIKA LINGKUNGAN BERDASARKAN PERSEPSI DI WELCOME AREA KAMPUS INSTITUT PERTANIAN BOGOR - Debora Budiyono (BUANA SAINS, 2015)
Welcome area on the campus of Bogor Agricultural University is an important element in an institutional area. Evaluation of environmental aesthetics done by the method of Scenic Beauty Estimation and the Semantic Differential. The purpose of the study: a) determine and assess the environmental quality of the area based on the shape and color of the tree; b) determining the level of beauty is based on the perception of the respondents; c) determine the preferences of respondents to the arrangement of landscape design welcome area based on the shape and color of the tree; and d) evaluate the visual quality of the landscape based on the estimation of beauty. The tools used: cameras, Photoshop CS 3 software, Minitab 16, and Acer 4741G. The study includes five stages: 1) the identification and study of the literature on the welcome area of IPB, 2) determining the location of the study, 3) making the landscape point (vantage point), 4) modification of existing photos based character visual closure, 5) assessment visitors through questionnaires. The concept of landscape which has the highest value to lower the concept of landscape 3 worth 91.1, the concept of landscape 4 worth 90.9, 2 worth 89.2, the concept of landscape 5 worth 78 and the lowest landscape landscapes existing concept of value 0. The highest concept is the concept of landscape 3, shows that the respondents wanted the landscape in accordance with the theme is a memorable landscape warm, cheerful, grand or large, formal, focused, open or bright, spacious, unique, and strong character. The landscape evaluation welcome IPB campus area, is expected to be a recommendation in the planning and design of the IPB campus